RETROSPECTIVE COMPARISON OF THREE‐DIMENSIONAL CONFORMAL RADIATION THERAPY VS. PREDNISOLONE ALONE IN 30 CASES OF CANINE INFRATENTORIAL BRAIN TUMORS. Issue 1 (15th November 2016) - Treggiari, Elisabetta; Maddox, Thomas W.; Gonçalves, Rita; Benoit, Jerome; Buchholz, Julia; Blackwood, Laura
Abstract : Infratentorial tumors are relatively infrequent in dogs and a lack of data makes it difficult to offer prognostic information. Untreated, dogs with these neoplasms have shorter survival times than those with supratentorial tumors. The role of radiation therapy (RT) in the management of infratentorial tumors is poorly defined and tumoral/peritumoral swelling in this site is a potential cause of serious acute side effects. The aim of this retrospective, cohort study was to describe cases of infratentorial tumors treated with fractionated three‐dimensional conformal RT (3D CRT) and glucocorticoids (GC), and compare outcomes and survival with dogs affected by tumors in the same location that received GC alone. Thirty patients with a MRI diagnosis of infratentorial tumors were recruited (15 received RT and GC and 15 GC alone). None had mentation changes at presentation. For both groups, MRI and medical records were reviewed; and factors associated with survival were evaluated with Kaplan–Meier product limit survival and Cox regression analysis. Overall median survival time (MST) was 294 days (95% CI 42–545). The MST in the RT group was 756 days (95% CI 209–1302) vs. 89 days (95% CI 34.7–143.3 days) for those dogs treated palliatively with GC alone. This difference was statistically significant ( P = 0.001). No other factors (including neurological signs, MRI features, tumor volume and total RT dose) were statistically associated with survival in the RT group. This study suggests that 3D CRT offers a survival advantage for dogs with infratentorial tumors compared to GC alone, and significant complications are uncommon.